2017
DOI: 10.3892/or.2017.5791
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli inhibit cervical cancer cell migration in vitro and reduce tumor burden in vivo through upregulation of E-cadherin

Abstract: The present study was designed to investigate the antitumor effects of Lactobacillus and the potential mechanisms. Cell Counting Kit-8 (CCK-8) assays were carried out to determine suitable doses for investigating the inhibitory effect of lactobacilli on cell migration ability of HeLa and U14 cells in vitro. In addition, western blot assays were performed to investigate the possible mechanisms corresponding to its antitumor effects. Furthermore, a xenograft mouse model was established for investigating the E-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Many clinical studies found that a decline in the quantity and activity of Lactobacillu s was involved in the initiation and progression of cervical cancer, which provides a novel insight into the use of probiotics to prevent cervical cancer. 47 , 54 , 58 Some experimental studies found that Lactobacillu s and its metabolites inhibit the proliferation of cervical cancer cells by regulating cancer-related genes or through an immunological mechanism. These studies provide a theoretical basis for further clinical application of Lactobacillus in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical studies found that a decline in the quantity and activity of Lactobacillu s was involved in the initiation and progression of cervical cancer, which provides a novel insight into the use of probiotics to prevent cervical cancer. 47 , 54 , 58 Some experimental studies found that Lactobacillu s and its metabolites inhibit the proliferation of cervical cancer cells by regulating cancer-related genes or through an immunological mechanism. These studies provide a theoretical basis for further clinical application of Lactobacillus in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin and N-cadherin are well known to be vital for normal cell adhesion, homeostasis, and tissue integrity. Recently, Li et al 31 reported that elevation of E-cadherin relieves tumor burden and suppresses migration of cervical cancer cells. MMPs are related with HPV infections in cervical cancer patients, among which MMP2 and MMP9 are associated with poor prognoses in patients with invasive cervical cancer, and their knockdown decreases migration of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus is an important probiotic that contributes to the immunity and health of animals. Their probiotic properties play an important role in regulating gut microbiota ( Igor et al, 2019 ), relieving intestinal diseases ( Sanders et al, 2019 ), and enhancing body immunity ( Garcia-Castilla et al, 2019 ) in addition to other functions ( da Costa et al, 2016 ; Li et al, 2017 ). Lactobacillus is known to protect hosts against intramammary infection in both humans and cows by oral or intramammary administration ( Jiménez et al, 2008 ; Arroyo et al, 2010 ; Fernández et al, 2016 ), but the mechanism of this protective effect remains unclear.…”
Section: Introductionmentioning
confidence: 99%